Immersive Learning Technologies in Education: A Systematic Review of Augmented Reality and Virtual Reality for Conceptual Understanding - Neni Sriwahyuni; Muharleni (Journal of Learning Innovation and Educational Technology, 2026)
The growing adoption of Augmented Reality (AR) and Virtual Reality (VR) has transformed educational technology by providing immersive learning environments that promote interactive and meaningful learning experiences. Despite increasing interest in these technologies, previous studies have reported inconsistent findings regarding their effectiveness in enhancing students' conceptual understanding, highlighting the need for a comprehensive synthesis of current evidence. This study aims to systematically review empirical research on the educational applications of AR and VR, with particular emphasis on their impact on conceptual understanding, supporting factors, implementation challenges, and pedagogical implications. A Systematic Literature Review (SLR) was conducted following the PRISMA 2020 guidelines. Scientific articles published between 2015 and 2025 were retrieved from Scopus, Web of Science, ScienceDirect, SpringerLink, ERIC, and Google Scholar using predefined inclusion and exclusion criteria. Of the 436 studies initially identified, 36 peer-reviewed articles met the eligibility criteria and were included in the thematic synthesis. The findings indicate that AR and VR consistently improve conceptual visualization, learner engagement, motivation, and experiential learning. However, their effectiveness in promoting conceptual understanding remains inconsistent and is strongly influenced by instructional design quality, pedagogical integration, cognitive load management, teacher competence, technological infrastructure, and learner readiness. The review further reveals that immersive technologies produce more meaningful learning outcomes when integrated with active learning approaches, such as inquiry-based, problem-based, and project-based learning, rather than functioning solely as visualization tools. This study proposes a conceptual framework that positions instructional design, pedagogical strategies, and implementation readiness as key determinants of successful immersive learning. These findings contribute to the advancement of educational technology literature and provide practical guidance for educators, instructional designers, and policymakers in developing pedagogically meaningful and sustainable AR- and VR-supported learning environments.